2020
DOI: 10.1001/jamanetworkopen.2019.21429
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mobile Patient Portal Access With Diabetes Medication Adherence and Glycemic Levels Among Adults With Diabetes

Abstract: IMPORTANCE Online patient portals support self-management, and mobile devices expand portal access, but whether this translates to improvements in diabetes outcomes is unclear.OBJECTIVE To examine the association of adding mobile patient portal access with diabetes medication adherence and glycemic levels among adults with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…Although over 1100 diabetes-related smartphone apps are currently available [ 27 ], and prior studies [ 6 , 10 - 13 , 28 , 29 ] have emphasized their impact on HbA 1c , there are limited data available on improving self-care skills or other clinical endpoints in patients with type 2 diabetes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although over 1100 diabetes-related smartphone apps are currently available [ 27 ], and prior studies [ 6 , 10 - 13 , 28 , 29 ] have emphasized their impact on HbA 1c , there are limited data available on improving self-care skills or other clinical endpoints in patients with type 2 diabetes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patient engagement is a set of behaviors by patients, family members, health professionals, and a set of organizational policies and procedures that foster the inclusion of patients and family members as active members of a collaborative healthcare team in partnership with providers and provider organizations [ 6 ]. Patient engagement translates to public health benefits on a larger scale because it results in increased levels of screening and preventive care, efficient utilization of health resources, and reduction in overall healthcare cost [ 5 , 7 ]. Linking patient portals to the aggregated data stored in Health Information Exchange systems, organizations can increase access to comprehensive patient records and improve population health surveillance and management [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…overall healthcare cost [5,7]. Linking patient portals to the aggregated data stored in Health Information Exchange systems, organizations can increase access to comprehensive patient records and improve population health surveillance and management [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, recent research has shown the importance of considering measures other than hemoglobin A1C, including time-in-range [14] and glycemic variability [15]. Previous research has also shown that the use of an online patient portal for web-based disease management can improve patient outcomes for diabetes [16][17][18][19][20][21] and prediabetes [22]. However, few PCPs utilize these portals [23].…”
Section: Introductionmentioning
confidence: 99%